Zoom Auxiliary Imaging Lens Design for a Modulation Transfer Function Test System - Yicheng Sheng; Sihan Xu; Caishi Zhang; Binghua Su; Dingxiang Cao; Zhe Chen (Photonics)
In this paper, we propose a zoom auxiliary imaging lens based on the four-component mechanical zoom method for a modulation transfer function (MTF) test system. The auxiliary imaging lenses of the current MTF test system typically use fixed-focus optical systems, which are unable to meet the test scenarios of fast and batch measurement and measure lenses with an extensive focal length range. Compared with the fixed-focus auxiliary imaging lens, the zoom auxiliary imaging lens can simultaneously satisfy the measurement of wide-angle and telephoto miniature lenses without losing measurement accuracy. The entrance pupil distance of the zoom lens is greater than that of traditional lenses, and it is constant for each focal length of the zoom lens. The zoom lens uses an intermediate real image surface to obtain the perfect image quality and lower the diameter of the rear group. Additionally, the zoom lens dynamically adjusts magnification to optimize image size and align with the detector’s pixel resolution, thereby preventing undersampling and enhancing measurement precision. The optical design is optimized for stability, delivering high resolution and minimal aberrations across the zoom range. The image quality of the zoom lens is nearly at the diffraction limit at each focal length, which significantly reduces the impact of the auxiliary lens on MTF test results, enhancing both flexibility and accuracy. This design is particularly well suited for testing miniature lenses in optoelectronic technology applications.